Evaluation of Hematological Profiles and Monocyte Subpopulations in Water Buffalo Calves after Immunization with Two Different IBR Marker Vaccines and Subsequent Infection with Bubaline alphaherpesvirus-1 - Francesco Grandoni; Jamal Hussen; Federica Signorelli; Francesco Napolitano; Maria Carmela Scatà; Immacolata De Donato; Giovanna Cappelli; Giorgio Galiero; Carlo Grassi; Esterina De Carlo; Stefano Petrini; Giovanna De Matteis; et al. (Vaccines, 2023)
Bubaline alphaherpesvirus-1 (BuAHV-1) and Bovine alphaherpesvirus-1 (BoAHV-1) are respiratory viruses that can cause an infection known as “Infectious Bovine Rhinotracheitis” (IBR) in both water buffalo and bovine species. As the main disease control strategy, vaccination can protect animals from clinical disease through the development of specific humoral and cell-mediated immune responses. In the present study, the time-related circulatory kinetics of hematological profile and bubaline monocyte subsets have been investigated in vaccinated buffalo calves after challenge infections with BuAHV-1. Thirteen buffalo calves were selected and grouped into the VAX-1 group, which received an IBR-live-attenuated gE-/tk-deleted marker vaccine; the VAX-2 group, which received an IBR-inactivated gE-deleted marker vaccine; the CNT group, which remained an unvaccinated control. Fifty-five days after the first vaccination, the animals were infected with 5 × 105.00 TCID50/mL of wild-type BuAHV-1 strain via the intranasal route. Whole blood samples were collected at 0, 2, 4, 7, 10, 15, 30, and 63 days post-challenge (PCDs) for the analysis of hematological profiles and the enumeration of monocyte subsets via flow cytometry. The analysis of leukocyte compositions revealed that neutrophils were the main leukocyte population, with a relative increase during the acute infection. On the other hand, a general decrease in the proportion of lymphocytes was observed early in the post-infection, both for the VAX-1 and VAX-2 groups, while in the CNT group, the decrease was observed later at +30 and +63 PCDs. An overall infection-induced increase in blood total monocytes was observed in all groups. The rise was especially marked in the animals vaccinated with an IBR-live-attenuated gE-/tK-deleted marker vaccine (VAX-1 group). A multicolor flow cytometry panel was used to identify the bubaline monocyte subpopulations (classical = cM; intermediate = intM; and non-classical = ncM) and to investigate their variations during BuAHV-1 infection. Our results showed an early increase in cMs followed by a second wave of intMs. This increase was observed mainly after stimulation with live-attenuated viruses in the VAX-1 group compared with the animals vaccinated with the inactivated vaccine or the non-vaccinated animal group. In summary, the present study characterized, for the first time, the hematological profile and distribution of blood monocyte subsets in vaccinated and non-vaccinated water buffalo in response to experimental infection with BuAHV-1. Although not experimentally proven, our results support the hypothesis of a linear developmental relationship between monocyte subsets.